2021
DOI: 10.1186/s12885-021-08560-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical margin width on long-term outcomes for intrahepatic cholangiocarcinoma: a multicenter study

Abstract: Background The objective of this study was to investigate the survival outcomes of surgical margin width in intrahepatic cholangiocarcinoma (ICC). Methods Between November 2011 and August 2017, patients who underwent hepatectomy for ICC were collected from 13 major hepatopancreatobiliary centers in China. The survival outcomes for patients who underwent wide margin hepatectomy (WMH) were compared with those who underwent narrow margin hepatectomy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Although these risk factors are usually comparable between groups in the studies we included, hierarchical analysis based on these risk factors is necessary, which may contribute to future treatment decisions. Studies have pointed out that CA-199 also has an impact on the prognosis of ICC; a lower level of CA-199 may be associated with a better prognosis, but the selection of different cutoff values leads to difficulties in data statistics [23,27]. In addition, hepatitis B virus infection is also considered to be associated with the prognosis of ICC in some studies, possibly because HBV infection can aggravate cirrhosis and reduce the volume of resectable liver [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these risk factors are usually comparable between groups in the studies we included, hierarchical analysis based on these risk factors is necessary, which may contribute to future treatment decisions. Studies have pointed out that CA-199 also has an impact on the prognosis of ICC; a lower level of CA-199 may be associated with a better prognosis, but the selection of different cutoff values leads to difficulties in data statistics [23,27]. In addition, hepatitis B virus infection is also considered to be associated with the prognosis of ICC in some studies, possibly because HBV infection can aggravate cirrhosis and reduce the volume of resectable liver [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor stage is one of the most critical factors impacting the prognosis of ICC [47]. Despite the fact that many studies suggest that tumor stage is a predictive factor for ICC, only Liu et al revealed a link between tumor stage and survival [23]. Only patients in AJCC stage I with a large margin can enhance survival, according to Liu et al, while patients in AJCC stages II and III cannot benefit from a broad margin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies recommend that anatomical liver resection or wide resection margin is a priority for HCC patients with MVI (27)(28)(29)(30). In ICC patients, many studies suggested that a wide surgical margin may lead to favorable survival benefits (7,(31)(32)(33). Hu et al (32) reported that very early recurrence (defined as recurrence within 6 months) after ICC hepatectomy mostly occurred in the surgical margin site.…”
Section: Discussionmentioning
confidence: 99%
“…Spolverato et al found that one of six patients undergoing a hepatic resection due to ICC will have a positive margin, which was associated with a poor OS [ 37 ]. The impact of surgical margin width on long-term survival has been up to debate and was recently investigated by Liu et al in a multicenter study [ 38 ]. They found that a surgical margin of 10 mm or more was associated with a longer OS of 41 months compared to 22 months in patients with a narrow surgical margin of less than 10 mm.…”
Section: Surgerymentioning
confidence: 99%